Effectiveness of Applying Jigsaw Type Problem Based Learning Model to Improve Student Activity and Learning Outcomes at SMAN 12 Makassar - Mustari, Mustari; Arisah, Nur (International Journal of Education, Vocational and Social Science, 2025)
This study aims to observe the improvement of student engagement in learning through the application of the Jigsaw-type Problem Based Learning (PBL) model. The method used in this research is qualitative, with the subjects being students from class X.6 in the 2024/2025 academic year. The implementation of the Jigsaw-type PBL model in the Sociology learning process emphasizes finding solutions to the problems presented, as an effort to understand the subject matter and enhance student engagement. The data collection techniques used include observation, documentation, and literature review. Based on the research findings and data analysis, it can be concluded that the application of the Jigsaw-type PBL model effectively increases student engagement in class X.6 at SMA Negeri 12 Makassar during the 2024/2025 academic year.